1995
DOI: 10.1016/0029-7844(94)00382-n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the rhd genotype in fetuses at risk for rhd hemolytic disease

Abstract: The objective of this study was to evaluate the accuracy of a DNA-based testing methodology in determining the RhD genotypes of fetuses at risk for RhD hemolytic disease. We designed a multiplex polymerase chain reaction-based test based on recent RhD and RhCE sequence information. To improve the accuracy of the results, two different portions of the RhD gene were examined. Deoxyribonucleic acid was extracted from fetal specimens, portions of the RhD gene were amplified by the polymerase chain reaction, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The frequency of false-negative (and false-positive, see above) events should be considerably reduced (or avoided) if at least two pairs of primers probing different regions of the RHD gene are used in routine analysis. Such an approach has been recently considered (Spence et al, 1995;Pope et al, 1995), but without a documented comparison of the different systems. The policy in our Centre is to simultaneously use all four typing methods separately, performed by two different investigators, each exploring only two methods.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of false-negative (and false-positive, see above) events should be considerably reduced (or avoided) if at least two pairs of primers probing different regions of the RHD gene are used in routine analysis. Such an approach has been recently considered (Spence et al, 1995;Pope et al, 1995), but without a documented comparison of the different systems. The policy in our Centre is to simultaneously use all four typing methods separately, performed by two different investigators, each exploring only two methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a DNA-based genotyping error can have serious consequences to the fetus if recommendations were made to withdraw therapy (Lighten et al, 1995). Therefore, it has been suggested that RhD genotyping of the fetus be performed by evaluating different regions of the gene to avoid genotyping errors (Aubin et al, 1997;Lighten et al, 1995;Pope et al, 1995;Simsek et al, 1994Simsek et al, , 1995Spence et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…To date, most experiences have been obtained using PCR on amniocytes. Previous studies 12–14 showed a nearly perfect correlation between the results of fetal RhD geno‐ and serotyping in a total of 237 pregnancies (error rates 0–1.4%).…”
Section: Discussionmentioning
confidence: 86%
“…For clinical application, we therefore analysed amniotic fluid specimens in two separate duplex PCR assays each detecting a different RhD gene region (exon 7 and exon 10). Spence et al 14 and Pope et al 23 preferred multiplex PCR, simultaneously amplifying RhD specific DNA fragments at exon 4 through 5 and exon 10. In contrast to these and other study groups, we used fluorescence PCR and automated DNA fragment analysis allowing rapid and objective testing.…”
Section: Discussionmentioning
confidence: 99%